IMF Staff papers, Volume 42 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes early contributions of Staff Papers to international economics. The paper highlights that Staff Papers has, since its inception in 1950, been an important vehicle for the dissemination of research done by the IMF staff. This paper discusses three areas in which articles published in Staff Papers up until the 1970s made major contributions to the literature in international economics. The areas covered are: the absorption approach and the monetary theory of the balance of payments; the Mundell-Fleming model; and foreign trade modeling.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet